Optimal Portfolio Choice with Predictability in House Prices and Transaction Costs - Corradin, Stefano; Fillat, José L.; Vergara-Alert, Carles (Review of Financial Studies, 2014)
We develop and solve a model of optimal portfolio choice with transaction costs and predictability in house prices. We model house prices using a process with a time-varying expected growth rate. Housing adjustments are infrequent and characterized by both the wealth-to-housing ratio and the expected growth in house prices. We find that the housing portfolio share immediately after moving to a more valuable house is higher during periods of high expected growth in house prices. We also find that the share of wealth invested in risky assets is lower during periods of high expected growth in house prices. Finally, the decrease in risky portfolio holdings for households moving to a more valuable house is greater in high-growth periods. These findings are robust to tests using household-level data from the Panel Study of Income Dynamics (PSID) and Survey of Income and Program Participation (SIPP) surveys. The coefficients obtained using model-simulated data are consistent with those obtained in the empirical tests.